Research progress in the pathogenesis of keloids - Kunpeng JIA; Jing ZHOU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
During the process of skin wound healing, hyperproliferation of fibroblasts and excessive deposition of collagen in the extracellular matrix lead to the formation of keloid, a benign tumor with characteristics of aggressive growth. Keloid is a challenging medical problem. The therapeutic efficacies of most conventional approaches are unsatisfactory. Keloid has a higher recurrence rate with a complex pathogenesis. This article reviews the progress of research in the formation of keloid, including inflammation, mechanical forces, epigenetic modification and so on, Studies show that interaction of multiple factors is involved in the formation of keloid, including inflammatory cells (neutrophils, macrophages, mast cells and T lymphocytes), inflammatory cytokines (interleukin-6, TGF-β and TNF-α), integrin signaling pathway, TGF-β/Smad signaling pathway, Rho-GTPase, YAP/TAZ, Wnt/β-catenin signaling pathway, epigenetic modification and adiponectin. The intervention of these factors is expected to become a new approach for the treatment of keloid.